Synthesis and electron−phonon interactions of Ce3+-doped YAG nanoparticles - Tok, Alfred Iing Yoong (2012)
Nanoparticles of cerium-doped yttrium aluminum garnet (YAG:Ce3+) phosphors were synthesized by a nonhydrolytic solvothermal method yielding particle sizes less than 10 nm. Oleic acid and oleylamine effectively capped the nanoparticles during the synthesis and allowed crystallization of garnet to take place at 300 °C. This facile approach will find wide acceptance and could be used in synthesizing other complex oxide nanoparticles. Studies on electron−phonon interactions in the nanoparticles have been carried out by fitting the observed optical spectra with the multimode Brownian oscillator model. Compared to the same material of larger particle sizes (30 nm, 250 nm, and bulk), the electron−phonon coupling strength is found to be much weaker.